(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Although pulmonary rehabilitation (PR) is a crucial part of managing chronic obstructive pulmonary disease (COPD), patients in India still have limited access to it. Additionally, it is not yet known what the ideal level of aerobic exercise intensity is for PR regimens. Consequently, the purpose of this research was to examine the impact of aerobic training at 60% and 80% of MWR on HRQOL, symptom management, and exercise capacity in chronic obstructive pulmonary disease (COPD) patients. The 34 patients with stable chronic obstructive pulmonary disease (COPD) were randomly allocated to one of two groups: 60% or 80% MWR, in this single-center, randomized non-inferiority/equivalence experiment performed in India. With the only difference being the degree of aerobic activity, all groups had 20 sessions of organized outpatient physical rehabilitation. The St. George’s Respiratory Questionnaire (SGRQ) was used to evaluate HRQOL, which was the main outcome measure. Results from the secondary outcomes included dyspnea as measured by Mahler’s Transitional Dyspnea Index, functional performance as evaluated by the London Chest Activity of Daily Living (LCADL) scale, and exercise tolerance as assessed by the six-minute walk test (6MWT), incremental exercise test (IET), and constant load exercise test (CLET). A modified intention-to-treat strategy was used for data analysis. Changes in both groups were more than the minimum clinically relevant difference (MCID), and they were statistically significant across the board. The two workout intensities did not vary significantly from one another. HRQOL, dyspnea, and exercise capacity all showed significant improvements as compared to baseline in the within-group studies. There were little side effects and strong adherence to the rehabilitation regimen. In chronic obstructive pulmonary disease (COPD) patients, pulmonary rehabilitation significantly improved exercise tolerance, symptom load, and quality of life, even when aerobic training was done at 60% or 80% of maximal work rate. Based on these results, aerobic exercise at a lower intensity may be adequate, if not preferred, for regular clinical use.